Theoretical Evidence of the Singlet Predominance in the Intramolecular Energy Transfer in Ruhemann's Purple Tb(III) Complexes. Issue 3 (10th February 2021) - Moura, Renaldo T.; Oliveira, Jhulie A.; Santos, Inácio A.; de Lima, Ewerton M.; Carlos, Luís D.; Aguiar, Eduardo C.; Neto, Albano N. Carneiro
Abstract: This work presents a theoretical study on the geometries and intramolecular energy transfer (IET) process of Tb 3+ ‐complexes based on the Ruhemman's purple (RP) as ligands. Density functional theory and its time‐dependent extension are performed to examine the coordination energies and excited states using the ωB97X‐D3/MWB54/def2‐TZVP/polarizable continuum model level of theory. The inclusion of solvent effect causes a blueshift in all excitation energies, which is crucial for a better description of the electronic situations of RP isomers and coordination compounds. The IET rates are assessed for 18 Tb‐RP different compounds, each one with 44 IET pathways, also, it is obtained that the main energy transfer channel comes from the singlet state, in complete agreement with previous experimental data. The energy transfer from the singlet state is mainly composed of the nonradiative absorptions 7 F6 → 5 G6 and 7 F5 → 5 G5, representing together 97% of the total IET rate. As far as it is known, this is the first time that the solvent effect is included in the IET rates calculation, registering a step toward the development of IET analysis without any experimental or phenomenological input data. Abstract : This work shows the predominance of the energy transfer rates from the singlet state over the triplet one in Tb(III) coordination compounds with Ruhemman's purple as ligands. The inclusion of solvent effect is important to the estimation of the energies of the excited states and it reflects directly in the intramolecular energy transfer rates.